Chemical cauterization of peristomal granulomas with 50% trichloroacetic acid (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objetive: This study deals with the treatment of granulomas, one of the possible complications of the stomies, which are characterized as focal lesions, whose formation occurs due to the presence of aggressive agents to the tissues from the increase of the degree of cellularity and other tissue elements, generating annoyance and anxiety to patients. This study aims to describe the clinical results of the treatment of peristomal granulomas with the use of 50% trichloroacetic acid (TCA). Methods: This is a case series study, carried out by professionals in a referral center for the treatment of individuals with an ostomy in the city of Porto Alegre, state of Rio Grande do Sul. Results: The study sample consisted of 13 patients who underwent follow-up for treatment of peristomal granulomas with TCA. Data collection was performed during nursing consultations, based on the observation and photographic record of the granulomas, with subsequent evolution in the individual charts. Conclusion: It was concluded from this study that the regular treatment with TCA resulted in regression of the granulomas until their total disappearance, being this acid able to be considered, therefore, a potential therapeutic option; however, it is recommended to carry out further studies on its use in stomatherapy, seeking the use of more robust clinical research methodologies and with bias control.